Effect of tillage, residue and nitrogen management on soil physical properties, root growth and productivity of wheat (Triticum aestivum) - BAG, KOUSHIK; Bandyopadhyay, K K; SEHGAL, V K; Datta, S P; SARANGI, A; PANDEY, R; KRISHNAN, P (The Indian Journal of Agricultural Sciences, 2020)
A study was conducted on a semi-arid climate and sandy loam soils of Indian Agricultural Research Institute farm, New Delhi to evaluate the short-term (5 years) interactions of tillage, residue and nitrogen management on soil physical properties, root growth and yield of wheat (Triticum aestivum L.) in a maize-wheat cropping system in a split-split plot design comprising two tillage (No tillage and conventional tillage), two residue levels (no residue, maize residue @ 5 t ha-1) and three nitrogen doses (N60, N120 and N180) as the main plot, sub plot and sub subplot treatments, respectively. It was observed that bulk density (up to 45 cm), penetration resistance (10-27 cm depth) reduced under no tillage and residue applied plots while the porosity (15-60 cm), mean weight diameter (0-15 cm), organic carbon (0-15 cm) improved in these treatments. The hydraulic conductivity was significantly enhanced due to residue applications in the surface layers (0-15cm). Root growth parameters were improved under no tillage and crop residue mulching. Although neither tillage nor residue mulching could significantly influence the grain and biomass yield of wheat on two years of study (2017-18, 2018-19), yield increased significantly with increasing nitrogen doses. Thus no tillage, residue mulching with 150% recommended dose of nitrogen can be practised for maintaining a better soil physical health, root growth without any significant reduction in crop productivity compared to conventional tillage.